2017
DOI: 10.1002/cyto.b.21526
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of immunophenotyping performed in cryopreserved peripheral whole blood

Abstract: Given this, cryopreserved blood should be considered a feasible biospecimen in clinical and epidemiological studies requiring leukocyte immunophenotyping. © 2017 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 30 publications
7
49
0
Order By: Relevance
“…Cryopreservation also provides further benefit in that biospecimens can be analyzed in large batches, minimizing overall analytical variability; this is especially important for studies in which collection occurs over a long period of time, or a large number of samples are obtained. Recently, we and others showed that cryopreserved peripheral blood, a biospecimen that is simple and inexpensive to prepare, is comparable to fresh blood for the enumeration of a number of leukocyte types, including monocytes, neutrophils, B‐lymphocytes, T‐cells, natural killer, and (NK)‐cells; our study also showed that these measures were also comparable to that obtained from cryopreserved peripheral blood mononuclear cells (PBMCs) or a hematology analyzer. However, many of these cell types, especially monocytes, T‐cells, and NK‐cells, are known to represent distinct groups of subsets that have specific roles in maintaining health and preventing disease.…”
supporting
confidence: 72%
See 4 more Smart Citations
“…Cryopreservation also provides further benefit in that biospecimens can be analyzed in large batches, minimizing overall analytical variability; this is especially important for studies in which collection occurs over a long period of time, or a large number of samples are obtained. Recently, we and others showed that cryopreserved peripheral blood, a biospecimen that is simple and inexpensive to prepare, is comparable to fresh blood for the enumeration of a number of leukocyte types, including monocytes, neutrophils, B‐lymphocytes, T‐cells, natural killer, and (NK)‐cells; our study also showed that these measures were also comparable to that obtained from cryopreserved peripheral blood mononuclear cells (PBMCs) or a hematology analyzer. However, many of these cell types, especially monocytes, T‐cells, and NK‐cells, are known to represent distinct groups of subsets that have specific roles in maintaining health and preventing disease.…”
supporting
confidence: 72%
“…Hence, absolute estimates of that leukocyte subset (calculated as the relative proportion multiplied by the total leukocyte count) would also be inflated. Proportional estimates relative to PBMCs would be expected to be more accurate given the reduced cellular loss in the PBMC compartment (as we have shown ), which would relate to better accuracy of absolute estimates. To enumerate total PBMCs, cryopreserved blood was thawed on ice for 20 minutes and 100 μl was transferred to a 2.0 ml snap‐top tube.…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations